1999
DOI: 10.1007/s002530051449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and pH on growth and product formation of Lactococcus lactis ssp. lactis ATCC 19435 growing on maltose

Abstract: Link to publicationCitation for published version (APA): Hofvendahl, K., van Niel, E., & Hahn-Hägerdal, B. (1999). Effect of temperature and pH on growth and product formation of Lactococcus lactis ssp. lactis ATCC 19435 growing on maltose. Applied Microbiology and Biotechnology, 51(5), 669-672. https://doi.org/10.1007/s002530051449General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…In previous studies fixed acids have been shown to be formed when lactococci metabolize maltose (24,42,47). To investigate whether formation of mixed acid products from maltose is related to growth, formation of products by four strains of L. lactis was studied during growth in semidefined medium (55) and in resting cell experiments (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies fixed acids have been shown to be formed when lactococci metabolize maltose (24,42,47). To investigate whether formation of mixed acid products from maltose is related to growth, formation of products by four strains of L. lactis was studied during growth in semidefined medium (55) and in resting cell experiments (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The first enzyme in the pathway, PFL, converts pyruvate to formate and acetyl coenzyme A, which is further metabolized to either ethanol or acetate. PFL is inactive in the presence of oxygen and at a low pH (24,35). With an active PFL pathway, three molecules of ATP are conserved per hexose molecule catabolized, compared with the two ATP molecules conserved per hexose molecule when LDH is used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1.73 ± 0.14 270 ± 41 46.6 ± 2.1 210.3 ± 1.2 homolactic to heterolactic fermentation for certain lactobacilli (Borch et al, 1991;Torino et al, 2001) and lactococci (Hofvendahl et al, 1999) and from acidogenesis to solventogenesis in ABE fermentation by C. acetobutylicum (Girbal et al, 1995;Rogers and Gottschalk, 1993). Different patterns of organic acid production were also observed in C. sporogenes fermentation at different pHs, and butyric acid production was favored at pH 5.5 (Montville et al, 1985).…”
Section: Effect Of Ph On Metabolic Pathwaymentioning
confidence: 99%
“…The references [19][20][21] have proved that two-stage pH control strategy was effective for the other products' accumulation such as pyruvate and transglutaminase, and Song and Chang investigated the effect of pH on ILE fermentation [11,12]. On the basis of two-stage agitation speed control strategy, fermentation was conducted at various pH values (5.7, 6.2, 6.7, 7.2, 7.7 and 8.2) in order to investigate the effects of pH on ILE fermentation.…”
Section: Development Of a Two-stage Agitation Speed Control Strategy mentioning
confidence: 99%